2022
DOI: 10.1101/2022.02.28.482242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress induced TDP-43 mobility loss independent of stress granules

Abstract: TAR DNA binding protein 43 (TDP-43) is closely related to the pathogenesis of amyotrophic lateral sclerosis (ALS) and translocates to stress granules (SGs). The role of SGs as aggregation-promoting 'bioreactor' for TDP-43, however, is still under debate. We analyzed TDP-43 mobility and localization under different stress and recovery conditions using live cell single-molecule tracking and super-resolution microscopy. Besides reduced mobility within SGs, a stress induced decrease of TDP-43 mobility in the cytop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…40 However, other work has suggested that aggregation occurs outside rather than inside stress granules and has proposed that stress granules might protect against aggregation. 24,[41][42][43][44][45][46] These disparate results have made it difficult to come to any general conclusions about the role of stress granule condensates in TDP-43 aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…40 However, other work has suggested that aggregation occurs outside rather than inside stress granules and has proposed that stress granules might protect against aggregation. 24,[41][42][43][44][45][46] These disparate results have made it difficult to come to any general conclusions about the role of stress granule condensates in TDP-43 aggregation.…”
Section: Introductionmentioning
confidence: 99%